ON THE EFFICACY OF A COMPUTER‐BASED PROGRAM TO TEACH VISUAL BRAILLE READING. Issue 2 (20th May 2013) - Scheithauer, Mindy C.; Tiger, Jeffrey H.; Miller, Sarah J.
Abstract Scheithauer and Tiger (2012) created an efficient computerized program that taught 4 sighted college students to select text letters when presented with visual depictions of braille alphabetic characters and resulted in the emergence of some braille reading. The current study extended these results to a larger sample (n = 81) and compared the efficacy and efficiency of the instructional program using 2 different response modalities. One variation of the program required a response in a multiple‐choice format, and the other variation required a keyed response. Both instructional programs resulted in increased braille letter identification and braille reading. These skills were maintained at a follow‐up session 7 to 14 days later. The mean time needed to complete the program was 22.8 min across participants. Implications of these results for future research, as well as practical implications for teaching the braille alphabet, are discussed.